Influence of the Gulf of Guinea Islands on the Atlantic Equatorial Undercurrent Circulation. Issue 9 (23rd September 2022) - Napolitano, D. C.; Alory, G.; Dadou, I.; Morel, Y.; Jouanno, J.; Morvan, G.
Abstract: In the easternmost portion of the Gulf of Guinea, Bioko Island marks the beginning of an island chain that stretches NE–SW to the Equator, where São Tomé Island sits in the path of the Equatorial Undercurrent (EUC). In this study, we explore the meso‐to‐large‐scale effects of local flow‐topography interactions that escalate from the EUC encounter with the Gulf of Guinea islands. A mean shipboard Acoustic Doppler Current Profiler section captures the EUC as a strong subsurface jet that ultimately hits São Tomé. Motivated by these observations, we ran two ocean general circulation model simulations that differ by the presence versus absence of the Gulf of Guinea islands. Diagnostics of salinity and potential vorticity (PV) from these simulations show that the EUC bifurcates at 6°E, triggering mesoscale activity that spreads the EUC waters. On both sides of São Tomé, the EUC branches roll up into eddies that propagate westward. These low‐PV anticyclones carry high salinity through the tropical Atlantic, introducing PV anomalies along eddy corridors mirrored by the Equator. The formation of such eddies is affected by diapycnal and isopycnal mixing and friction, and their distribution between hemispheres is intrinsically related to the location of São Tomé. The eddies are modulated at both seasonal and interannual scales. A strong EUC generates numerous and stronger eddies, while seasonal equatorial upwelling indirectly hinders their formation. Convergence of the EUC upstream of São Tomé reveals intense downwelling and freshening, whereas divergence and upwelling are associated with the EUC negotiating the island. Plain Language Summary: In the eastern portion of the tropical Atlantic, in the Gulf of Guinea, Bioko Island marks the beginning of an island chain that stretches NE–SW to the Equator, where São Tomé Island sits in the path of the strongest current in the tropical Atlantic, the Equatorial Undercurrent (EUC). The EUC connects the tropical Atlantic, transporting high‐salinity waters eastward. In this study we explore the effects of flow‐topography interactions on the EUC circulation. Velocity observations capture the EUC as a strong current that hits São Tomé Island. Motivated by these observations, we ran two model simulations that differ by the presence versus absence of the Gulf of Guinea islands. Diagnostics of salinity and potential vorticity (a dynamical quantity that relates to the circulation) show that the EUC bifurcates at 6°E, spreading the EUC waters. On both sides of São Tomé Island, the EUC branches form eddies that propagate westward through the tropical Atlantic. The formation and distribution of such eddies present an asymmetry between hemispheres due to the EUC interaction with São Tomé. On regional scales, a particle‐tracking experiment reveals sinking before the particles reach São Tomé, with mixing and freshening of the EUC waters as they flow around the island. Key Points: Velocity observations show that the Equatorial Undercurrent (EUC) hits São Tomé Island at 6°E, forcing the jet to bifurcate earlier than if the island did not exist The EUC dynamics and the location of São Tomé impose an asymmetry to the bifurcation, affecting net zonal fluxes in the tropical Atlantic The EUC‐island encounter triggers vertical advection and transformation of the EUC water via diapycnal and isopycnal mixing and friction